(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
This article discussed graphic stylistic devices in the English and Uzbek languages, the connotational meanings expressed in them. Graphic-stylistic devices in English and Uzbek have been analyzed on the basis of examples from poetic and prose works in both languages. Attention is also paid to the fact that graphic stylistic devices are represented by various punctuation marks.